Monitoring Water Storage System Based Internet of Things (IoT) - Norzari, Nor Azrie; Fuad, Norfaiza (Evolution in Electrical and Electronic Engineering, 2023)
The Monitoring Water Storage System Based Internet of Things (IoT) is a water level monitoring system specially designed for water tanks at home to solve the problem for residential households to prepare for the water shortage. The system is built to monitor the tank's water level and prepare them to save the remaining water inside the tank if any unwanted things happen during the time. This system is designed using HC-SR04 ultrasonic sensor, a solenoid valve, and the Blynk IoT platform. The ultrasonic sensor evaluates the water level in a tank and sends the data to the Blynk application, following the user to monitor the water level in real time. Furthermore, the system controls the solenoid valve to open and close the water flow based on the water level which the user has set the minimum and maximum value of the tank. The system has succeeded in monitoring the tank's low, medium, and high volumes of water. This system also can provide a cost-effective solution for monitoring and controlling the water level in a tank and can be used in various applications such as agricultural, residential, or commercial applications.